Estado, Dialética e Revoluções - inquirições sobre a tríade espiral da Modernidade - Carola Maria Marques de Castro (2017)
The present dissertation sought in a historical-philosophical reflection, to reconstruct the spirit of the Revolutionary State of modernity, in an attempt to understand the post-revolutionary State and sketch a possible Revolution in the current historical process. In the Age of Reason-modernity, Revolutions the proliferate, marking in the development of history man as subject of rights, as a reflection of the path of freedom of this and also as a contingency of history itself. These Revolutions were consolidated through the moment of denial known as Terror, a path capable of bringing the dialectical recomposition of the post-revolutionary State, which structures a mediation organization, through a legal-political framework that delimits power and rebuilds the citizen; Reinvents Democracy; Effective ethical maximum by the declaration of fundamental rights, but in a brief historical space is envisaged by poiethical State, returning the place of prominence to the subject, and thus begins to provoke a rupture of the post-revolutionary state. The internal contradiction of the state itself, combined with the consequences of the poiethical, makes the effectiveness of the ethical maximum impossible, and makes it a catalyst that leads to the exhaustion of the Democratic Rule of Law. In this line of reasoning is a concept of the present State possible? Whereas the present is the imminent breakdown of the Rule of Law? Is it still possible to think of revolution in the present State?